2013
DOI: 10.1021/ol401968m
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Catalytic Transannular Ketone–Ene Reactions

Abstract: Highly enantio- and diastereoselective transannular ketone-ene reactions are catalyzed by a new chromium(III) triflate tridentate Schiff-base complex. Electronically unactivated keto-olefins undergo hetero-ene reactions at ambient temperature to afford enantioenriched bicyclic alcohols, common structural motifs in natural products. The kinetic resolution of a configurationally stable planar-chiral cyclodecenone is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Because we only observed 8 instead of 12b from in vivo and in vitro experiments, therefore a spontaneous Alder-ene reaction may take place and convert 12b to 8 (Fig. 1 ) 21 , 22 . The selection of one component in equilibrium with another for biosynthesis is reminiscent of the biosynthesis of phosphonate from PEP, where a homocitrate synthase, FrbC, provides the thermodynamic driving force needed to pull the unfavorable PEP mutase reaction 23 .…”
Section: Resultsmentioning
confidence: 91%
“…Because we only observed 8 instead of 12b from in vivo and in vitro experiments, therefore a spontaneous Alder-ene reaction may take place and convert 12b to 8 (Fig. 1 ) 21 , 22 . The selection of one component in equilibrium with another for biosynthesis is reminiscent of the biosynthesis of phosphonate from PEP, where a homocitrate synthase, FrbC, provides the thermodynamic driving force needed to pull the unfavorable PEP mutase reaction 23 .…”
Section: Resultsmentioning
confidence: 91%
“…In particular, and after the seminal report by Jacobsen dealing with an elegant example of a transannular Diels–Alder reaction under chiral oxazaborolidine catalysis, only four additional transformations have been reported up to date. Jacobsen himself described an enantioselective transannular ketone–ene reaction using a salen—Cr(III) Lewis acid catalyst and Hierseman has reported the use of Cu(II)‐bis‐oxazoline compexes as catalysts in a transannular Claisen rearrangement . Alternatively, enamine catalysis has been used by List in a transannular aldol reaction, and some of us have also very recently reported one example of a catalytic and enantioselective transannular Morita–Baylis–Hillman reaction under chiral phosphine catalysis …”
Section: Methodsmentioning
confidence: 99%
“…In 2013, Jacobsen et al [92] synthesized highly enantioselective and diastereoselective transannular ketone-ene reactions using a novel Cr(III) triflate-Schiff base complex 101 a-101 d (5 mol %). They further confirmed that it could activate aldehydes in this reaction and ketones through single pot binding.…”
Section: Enantioselective Transannular Ketone-ene Reactionmentioning
confidence: 99%